HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KECEMASAN MAHASISWA KEPANITERAAN KLINIK FK UPN VETERAN JAKARTA - Abdul Wahid Adnan A (2022)
There are several variables that can affect the quality of your sleep, such as your environment, your health, the amount of exercise you do, and your general lifestyle. Compared to other college students, medical students are more likely to have sleep problems. Low-quality sleep may be linked to mental health issues such as anxiety. The clinical apprentice population is known to suffer from insomnia and panic episodes. Nonetheless, there is a dearth of recent research addressing this issue. The researcher wanted to find out how interns at UPN Veterans Medical College Jakarta rated their sleep quality in relation to their level of anxiety. This study used a cross-sectional strategy for descriptive analysis. The respondent's sleep quality will be assessed by the Pittsburgh Sleep Quality Index (PSQI) questionnaire used to assess the respondent's anxiety level using the Beck Anxiety Inventory (BAI) questionnaire. Respondents in this study amounted to 104 people with an average age of 22.63 years. The majority of respondents are female, as many as 78 (75%) people. The sleep quality of most of the respondents was good, as many as 61 (58.7%) people. The level of anxiety experienced by the majority of respondents was in the low category as many as 94 (90.4%) people. There was a significant relationship (p = 0.009) between sleep quality and anxiety level with weak correlation strength and positive correlation direction (r = 0.254). The better the quality of sleep, the lower the level of anxiety experienced.